Rare bird documentation form for Northern Goshawk at Hickory Hill Park, 1981 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1981)
Rare bird documentation form for a Northern Goshawk at Hickory Hill Park in Johnson County, IA on November 16, 1981. Epson - sheet feed